Economic and financial impact of large scale energy efficiency programme for housing using the European Union structural funds. The case of Lithuania - Galinienė, Birutė; Bumelytė, Junona; Markauskas, Ramūnas (Skutki finansowe i ekonomiczne programu wspierania energetycznej efektywności skali w mieszkalnictwie przy użyciu funduszy strukturalnych. Przypadek Litwy, 2011)
During the programming period of 2007-2013, the EU Cohesion Policy has started playing a new and important role in the process of supporting investments into energy efficiency measures in the housing sector, which plays a crucial part in achieving energy savings targets and combating climate change whilst contributing to energy savings and security. The increasing need for the effective renovation of housing stock, which was constructed during the period of cheap energy resources, is most notable in Central and Eastern Europe. The authors present calculations of the main financial indicators, i.e. net present value, internal rate of return, simple payback period, and the cost of conserved energy. Financial indicators are calculated based on the aims and the objectives of the Programme for Renovation of Multi-Apartment Buildings in Lithuania
Ekonomia = Economics, 2011, Nr 2 (14), s. 254-263
Keywords: European Union financial support; energy efficiency; housing